2015
DOI: 10.1007/s00198-015-3290-z
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, smoking cessation, and fracture risk in elderly women followed for 10 years

Abstract: Smoking increased the risk for fracture among elderly women, especially vertebral fractures. Smoking cessation decreased the risk for vertebral fractures but not for other types of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 39 publications
2
33
0
3
Order By: Relevance
“…This study, by use of genetic instruments, strengthens the causal inference on an association between smoking and higher fracture risk. Accordingly, by more firm scientific support, reducing cigarette smoking initiation and smoking cessation, considering the reversible risk of smoking on fracture risk [38,39], can now be even more strongly recommended for fracture prevention. No associations were observed between genetically predicted alcohol and coffee intake and fracture or BMD, but there was evidence that alcohol dependence may be a risk factor for fracture.…”
Section: Resultsmentioning
confidence: 99%
“…This study, by use of genetic instruments, strengthens the causal inference on an association between smoking and higher fracture risk. Accordingly, by more firm scientific support, reducing cigarette smoking initiation and smoking cessation, considering the reversible risk of smoking on fracture risk [38,39], can now be even more strongly recommended for fracture prevention. No associations were observed between genetically predicted alcohol and coffee intake and fracture or BMD, but there was evidence that alcohol dependence may be a risk factor for fracture.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced smoking is associated with a suppressed incidence of fractures [43], especially in the vertebral column [43, 81] and reduced prevalence of periodontal disease [82]. Smoking is the most detrimental modifiable risk factor that should be pro-actively managed [83].…”
Section: Interdisciplinary Management Of Osteoporosis and Periodontitismentioning
confidence: 99%
“…Our participants had a significant smoking history (46 pack-years for the COPD group, 32 for the smokers), indicating that smoking rather than COPD is a major risk factor for VFs. (11,38,39) In a group of 90 COPD patients (69 AE 1 years old, 60% male), Graat-Verboom et al (32) showed an increase of prevalent VFs from 32% to 52% within three years (63% increase). In our study population, prevalence of VFs increased from 20.4% at baseline to 24.5% at 1-year and 32.4% at 3-year follow-up (59% increase), indicating a similar increase.…”
Section: Comparison To Published Researchmentioning
confidence: 99%
“…(32) However, the incidence of clinical VFs in subjects with COPD was as low as 1.3/1000 person-years (35) to 6% over 2.6 years (36) and 0.5% to 1.0% within 3 years. (37) Smokers without COPD have lower BMD, (38) an increased risk of VFs, (11,24,34,38,39) and an increased risk of any osteoporotic fracture. (10,39) The prevalence of radiographic VFs in smokers as reported in the literature varied between 11% and 24%, (34,38) whereas incidence of clinical VFs varied from 3% (40) (30-year follow-up) to 26% (39) (10-year follow-up).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation